Validation of the DSCOVR Spacecraft Mission Space Weather Solar Wind Products. Issue 10 (30th September 2022) - Loto'aniu, Paul T. M.; Romich, K.; Rowland, W.; Codrescu, S.; Biesecker, D.; Johnson, J.; Singer, H. J.; Szabo, A.; Stevens, M.
Abstract: In this paper, we present a statistical validation of the Deep Space Climate Observatory (DSCOVR) solar wind data in the operational space weather archive. The DSCOVR observations of the interplanetary magnetic field (IMF), solar wind velocity, density, and temperature were hourly averaged and compared to measurements from NASA's Advanced Composition Explorer (ACE) and Wind spacecraft. Hourly averages, in general, show good correlations between the satellites for the IMF, solar wind velocity Geocentric Solar Ecliptic (GSE) v x ‐component, and density. During the period covered by this study (spanning from late July 2016, when DSCOVR went operational, to the end of 2020), the DSCOVR products show no clear evidence of permanent degradation. However, for plasma parameters, there were periods of disagreement with ACE and Wind . The correlation coefficients (Pearson's r ) calculated over the entire study period were similar or the same between DSCOVR versus Wind and DSCOVR versus ACE. For comparisons between DSCOVR and Wind, the IMF B x and B y GSE r were 0.94 and 0.96, respectively, while r for the IMF GSE B z ‐component was 0.88. For solar wind velocity, r was found to be 0.96 for the GSE v x ‐component, compared with 0.30 for v y and 0.33 for v z . For density, r was found to be 0.84. DSCOVR density observations tend to overestimate compared to Wind values when the solar wind densities are low (below ∼5/cc), while the agreement between the two spacecraft on IMF measurements tends to increase with decreasing spatial separation. Plain Language Summary: We present a statistical validation of space weather operational products derived from measurements onboard a National Oceanic and Atmospheric Administration (NOAA) spacecraft orbiting at about 1.5 million kilometers toward the Sun from Earth. Spacecraft observations of the solar wind magnetic field, velocity, density, and temperature were hourly averaged and compared to measurements from two other spacecraft in similar orbits. Hourly averages, in general, show good correlations between the spacecraft for solar wind magnetic field, the main component of velocity and density. However, for solar wind plasma parameters, there were periods of disagreement with the other two spacecraft. The NOAA spacecraft density observations tend to overestimate when compared to one of the other spacecraft measurements when the solar wind densities are low, while the agreement between these two spacecraft on magnetic field measurements tends to increase with decreasing spacecraft separation. Key Points: We validate the Deep Space Climate Observatory operational space weather data products Magnetic field data showed good statistical agreement with Wind and Advanced Composition Explorer (ACE) data Solar wind velocity Geocentric Solar Ecliptic v x ‐component and density also showed good statistical agreement with Wind and ACE data